PENINGKATAN PROSES DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING KELAS V SEKOLAH DASAR NEGERI 116/II EMPELU KECAMATAN TANAH SEPENGGAL - Avana, Nurlev; Wiyoko, Tri (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
The problem in this study is the learning process and student learning outcomes in grade V SDN 116/II Empelu are still low, this is evidenced by the results of preliminary observations made by researchers of 20 students only 35% who scored in the completed criteria. The cause is students in the passive class, have not used a varied learning model, and have not used concrete in learning. The researcher's aim is to improve the process and learning outcomes of the mathematics through the Application of the Problem Based Learning model. The research method used in this research is classroom action research. This class action research consists of two cycles, each cycle consisting of four stages of activity namely planning, implementing, observing and reflecting. Data collection with observation sheets for student learning process and tests for student learning outcomes. The results showed that the use of the TGT type of Cooperative Learning Model can increase student process and learning outcomes. This can be seen from the increase in student learning process, in the first cycle reached 55% categorized quite active and in the second cycle increased to 85%.